= sinA sinB = LS

= 1/2 * (2 * sinA sinB)

1/2[cos(A-B)-cos(A B)]

=1/2[(cosAcosB sinAsinB)-(cosAcosB-sinAsinB)]

=1/2[2sinAsinB]

=sinAsinB

cos(A-B)=cos(A)*cos(B) sin(A)*sin(B)

cos(A B)=cos(A)*cos(B)-sin(A)*sin(B)

cos(A-B)-cos(A B)= cos(A)*cos(B) sin(A)*sin(B)-

(cos(A)*cos(B)-sin(A)*sin(B))=

2*sin(A)*sin(B)

So sin(A)*sin(B)=0.5(cos(A-B)-cos(A B))

= sinA sinB = LS

1/2[cos(A-B)-cos(A B)]

=1/2[(cosAcosB sinAsinB)-(cosAcosB-sinAsinB)]

=1/2[2sinAsinB]

=sinAsinB

1/2[cos(A-B)-cos(A B)]

=1/2[(cosAcosB sinAsinB)-(cosAcosB-sinAsinB)]

=1/2[2sinAsinB]

=sinAsinB

cos(A-B)=cos(A)*cos(B) sin(A)*sin(B)

cos(A B)=cos(A)*cos(B)-sin(A)*sin(B)

cos(A-B)-cos(A B)= cos(A)*cos(B) sin(A)*sin(B)-

(cos(A)*cos(B)-sin(A)*sin(B))=

2*sin(A)*sin(B)

So sin(A)*sin(B)=0.5(cos(A-B)-cos(A B))

This post is last updated on hrtanswers.com at Date : 1st of September – 2022